Region-Specific Cerebral Metabolic Alterations in Streptozotocin-Induced Type 1 Diabetic Rats: An in vivo Proton Magnetic Resonance Spectroscopy Study. Issue 11 (November 2015) - Zhang, Hui; Huang, Mingming; Gao, Lifeng; Lei, Hao
Clinical and experimental in vivo 1 H-magnetic resonance spectroscopy ( 1 H-MRS) studies have demonstrated that type 1 diabetes mellitus (T1DM) is associated with cerebral metabolic abnormalities. However, less is known whether T1DM induces different metabolic disturbances in different brain regions. In this study, in vivo 1 H-MRS was used to measure metabolic alterations in the visual cortex, striatum, and hippocampus of streptozotocin (STZ)-induced uncontrolled T1DM rats at 4 days and 4 weeks after induction. It was observed that altered neuronal metabolism occurred in STZ-treated rats as early as 4 days after induction. At 4 weeks, T1DM-related metabolic disturbances were clearly region specific. The diabetic visual cortex had more or less normal-appearing metabolic profile; while the striatum and hippocampus showed similar abnormalities in neuronal metabolism involving N-acetyl aspartate and glutamate; but only the hippocampus exhibited significant changes in glial markers such as taurine and myo-inositol. It is concluded that cerebral metabolic perturbations in STZ-induced T1DM rats are region specific at 4 weeks after induction, perhaps as a manifestation of varied vulnerability among the brain regions to sustained hyperglycemia.